Multidomain Lifestyle Interventions for the Prevention of Cognitive Decline After Ischemic Stroke: Randomized Trial. Issue 10 (October 2015) - Matz, Karl; Teuschl, Yvonne; Firlinger, Bernadette; Dachenhausen, Alexandra; Keindl, Magdalena; Seyfang, Leonhard; Tuomilehto, Jaakko; Brainin, Michael
Abstract : Background and Purpose—: Cognitive impairment occurs in ⩽30% of all stroke survivors. However, effective therapies aimed at preventing poststroke cognitive decline are lacking. We assessed the efficacy of a multidomain intervention on preventing cognitive decline after stroke. Methods—: In this randomized, observer-blind trial patients were recruited within 3 months after an acute stroke in 5 Austrian neurological centers. Patients were assigned to a 24-month lifestyle-based multidomain intervention or standard stroke care. Primary outcomes were the cognitive subscale of the Alzheimer Disease Assessment Scale (ADAS-cog) and occurrence of cognitive decline in the composite scores of at least 2 of 5 cognitive domains at 24 months. Results—: A total of 101 patients were randomized into multi-intervention and 101 into standard care during June 2010 and November 2012. Of them, 76 patients in the intervention group and 83 in the control group were included in the final intention-to-treat analysis. At 24 months, 8 of 76 (10.5%) patients in the intervention group and 10 of 83 (12.0%) patients in the control group showed cognitive decline corresponding to a relative risk reduction of 0.874 (95% confidence interval, 0.364–2.098). The change in ADAS-cog from baseline to 24 months was not different either (median 0 [IQR, −1 to 2] in both groups; P =0.808). Conclusions—: This trial found no benefit of 24-month multidomain intervention with focus on improvement in lifestyle and vascular risk factors on the incidence of poststroke cognitive decline in comparison with standard stroke care. Studies with a larger sample size are needed. Clinical Trial Registration—: URL:http://clinicaltrials.gov . Unique identifier: NCT01109836. Abstract : Supplemental Digital Content is available in the text.